The Potential Effect of Gynura Procumbens Aqueous Extract as Anti-Hyperglycaemia, Pro-Fertility and Libido Agent Towards Diabetes-Induced Male Rats - Akmar, Khaidatul; Noor, Mahanem Mat (Proceeding International Conference on Science and Engineering, 2020)
Diabetes mellitus is a metabolic disorder that often affected fertility health, specifically in men. Gynura procumbens (G. procumbens) has been used as traditional medicine due to its ability in treating various types of illness. Hence, this study was carried out to determine the potential beneficial effect of G. procumbens as anti-hyperglycaemia, pro-fertility and libido agent towards diabetes-induced male rats. A total of 42 male Sprague Dawley rats were randomly assigned into six groups; normal, negative, and positive control, and three treated groups of different dosages of G. procumbens aqueous extract (GPAE); 150 mg/kg, 300 mg/kg and 450 mg/kg. Each group was given treatment via oral gavage for seven consecutive days. The rats were sacrificed on day eighth for further analysis. The fasting blood glucose (FBG) level in all GPAE treated group showed significant decrease, and 450 mg/kg treated group showed significant reduction to a normal blood glucose level compared to all groups. There were significant increases in the sperm quality of GPAE treated groups after seven days of treatment compared to the negative and positive control group, specifically in 450 mg/kg treated group. Testis histology showed that GPAE treated groups produced a significant result whereby the seminiferous tubules were seen packed with sperm and successive stage of spermatogenesis were shown compared to control groups. Hormone analysis suggested that the luteneizing hormone (LH), follicle stimulating hormone (FSH) and testosterone hormone of the treated groups were elevated after seven days of treatment compared to the negative and positive control groups. Libido analysis of seven days treatment showed that GPAE treated groups, significantly improved in 450 mg/kg dose compared to other groups, with the highest number of mounting frequency and shortest mounting latency. Fertility test revealed a significant increase in number of implantation sites produced in GPAE treated groups compared to positive and negative control groups. In conclusion, GPAE exhibited a potential beneficial effect as an anti-diabetic and also as fertility agent in diabetic-induced male rats.